Associations Between Religious/Spiritual Coping and Depression Among Adults with Cystic Fibrosis: A 12-Month Longitudinal Study - Sherman, Allen C. (Journal of religion and health, 2021)
Individuals with cystic fibrosis (CF) face a challenging disease, and depression is a significant concern. Many patients draw on religious/spiritual resources to assist them in managing the demands of chronic illness; however, these coping efforts rarely have been evaluated among adults with CF. This longitudinal study examined relationships between distinct types of positive and negative religious/spiritual coping at baseline (assessed with the RCOPE) and depression screening outcomes 12 month later (assessed with the Hospital Anxiety and Depression Scale). In logistic regression analyses controlling for disease severity (FEV1% predicted), lower likelihood of depression caseness at 12 months was predicted by higher general religiousness at baseline, greater use of benevolent religious reappraisal coping, greater use of spiritual connection coping, and lower spiritual discontent. Results suggest that distinct aspects religious/spiritual coping have differential associations with subsequent depression outcomes. Findings extend prior research to an important, understudied medical population, and address a clinically meaningful outcome.